Agent-based fuzzy constraint-directed negotiation mechanism for distributed job shop scheduling. (August 2016) - Hsu, Chia-Yu; Kao, Bo-Ruei; Ho, Van Lam; Lai, K. Robert
Abstract: This paper presents an agent-based fuzzy constraint-directed negotiation (AFCN) mechanism to solve distributed job shop scheduling problems (JSSPs). The scheduling problem is modelled as a set of fuzzy constraint satisfaction problems (FCSPs), interlinked by inter-agent constraints. Each FCSP represents the perspective of the participants and is governed by autonomous agents. The novelty of the proposed AFCN is to bring the concept of a fuzzy membership function to represent the imprecise preferences of task start time for job and resource agents. This added information sharing is crucial for the effectiveness of distributed coordination. It not only can speed up the convergence, but also enforce a global consistency through iterative exchange of offers and counter-offers. The AFCN mechanism can also flexibly adopt different negotiation strategies, such as competitive, win–win, and collaborative strategies, for different production environments. The experimental results demonstrate that the proposed model can provide not only high-quality and cost-effective job shop scheduling (i.e., comparable to that of centralized methods) but also superior performance in terms of the makespan and average flow time compared with other negotiation models for agent-based manufacturing scheduling. As a result, the proposed AFCN mechanism is flexible and useful for distributed manufacturing scheduling with unforeseen disturbances. Graphical abstract: Highlights: Agent-based fuzzy constraint-directed negotiation (AFCN) mechanism is proposed. To achieve autonomous cooperation for distributed job shop scheduling. AFCN mechanism is flexible to incorporate different negotiation strategies. AFCN mechanism outperforms both auction-based negotiation and the contract net protocol.